Developing talent in finance and accounting through social business - Aini Aman; Rusmaini Ramly (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
There is a need of specific talent development program to ensure the employability of accounting graduates especially in Finance and Accounting (F&A) Shared Service industry. Talents in F&A are still lacking to fuel the F&A shared service job markets as there was only 1 out of 10 accounting graduates being employed after interviewed for a job. This study aims to provide empirical understanding of talent development in F&A through social business. Specifically, the research questions are what are the hard skills and soft skills that could be developed through social business project and how can social business project assist in the development of talent for F&A. Using a case study of Technocount Project in the UKM Yunus Center of Advancement of Social Business (UKM-Yunus CASB), this study provides understanding on the talent development of accounting graduates through their apprenticeship in Social Business project. The social business project called Technocount provides accounting services to micro-businesses at minimal costs. Findings show that those involved in the project have sharpen their soft skills by participating in ‘real-business’ environment. Theoretically, this study improved our understanding on Social Business Model especially in talent development process. Practically, this study provides guidelines on how to develop talent through social business project.